Beyond Deforestation: Carbon Emissions From Land Grabbing and Forest Degradation in the Brazilian Amazon - Kruid, Sanne; Macedo, Marcia N.; Gorelik, Seth R.; Walker, Wayne; Moutinho, Paulo; Brando, Paulo M.; Castanho, Andrea; Alencar, Ane; Baccini, Alessandro; Coe, Michael T. (Frontiers in Forests and Global Change, 2021)
Carbon losses from forest degradation and disturbances are significant and growing sources of emissions in the Brazilian Amazon. Between 2003 and 2019, degradation and disturbance accounted for 44% of forest carbon losses in the region, compared with 56% from deforestation (forest clearing).Land tenure played a decisive role in carbon losses, with Undesignated Public Forests and Other Lands (e.g. private properties) accounting for the majority (82%) of losses.Illegal deforestation and land grabbing in Undesignated Public Forests are important and growing drivers of forest carbon emissions from the region. Indigenous Territories and Protected Natural Areas had the lowest emissions, demonstrating their effectiveness in preventing deforestation and maintaining carbon stocks.Monitoring and reporting carbon losses from forest degradation/disturbance will be crucial for Brazil to design effective climate mitigation strategies.